Application of failure mode and effect analysis in manufacturing industry - an integrated approach with FAHP-fuzzy TOPSIS and FAHP-fuzzy VIKOR. (2018) - Sakthivel, G.; Saravanakumar, D.; Muthuramalingam, T.
The objective of this paper is to evaluate greatest risk for production of dust cap in automotive industry based on FMEA and FAHP integrated with TOPSIS and VIKOR under fuzzy environment. FAHP is used to compute the weights of severity, occurrence and detection, whereas fuzzy TOPSIS and fuzzy VIKOR are used to obtain the final ranking of risk. The ranking of the failures depends upon the closeness coefficient of nine failure modes. The priority ranking order of failures for fuzzy TOPSIS and fuzzy VIKOR are F1 (0.649) > F2(0.5116) > F4(0.470) > F6(0.4128) > F3(0.4118) > F7(0.406) > F8(0.372) > F5(0.3445) > F9(0.3409) and F1(0) > F2(0.461) > F4(0.716) > F3(0.720) > F7(0.957) > F6(0.967) > F8(0.974) > F5(0.982) > F9 (1.000). Hence by comparing both these methods, F1(blanking of blank failure) and F2 (drawing dimension failure) are obtained as the most serious failure mode using fuzzy TOPSIS and fuzzy VIKOR.